(untitled) - FURQON, ACHMAD (Language Horizon: Journal of Language Studies, 2014)
PAULO’S SPIRITUAL IDENTITY IN PAULO COELHO’S ALEPH Achmad Furqon English Literature, Art and Language Faculty, State University of Surabaya lonelyliar91@gmail.com Dr. Ali Mustofa, SS., M.Pd. English Literature, Art and Language Faculty, State University of Surabaya ali_mustofa2005@yahoo.co.uk Abstrak Fokus permalasahan pembentukan identitas berkembang selama tahap dewasa . Permasalahan tersebut meliputi kejuruan, politik, agama / spiritual , dan seksualitas . Sebagai salah satu fokus permasalahan pembentukan identitas , spiritualitas mencakup isu-isu utama dalam pembentukan identitas pada tahap dewasa . Spiritualitas berkontribusi penting dalam pembentukan identitas. Spiritualitas membawa kesadaran diri dalam hubungan dengan orang lain. Melakukan aktivitas spiritual memberikan rasa keterhubungan dengan Tuhan , manusia , atau alam, memberikan kesempatan bagi individu untuk mnegenali dirinya sendiri dalam hubungannya dengan Tuhan , komunitas orang percaya , atau alam. Pencarian identitas spiritual Paulo telah menyebabkan dia untuk menuntaskan proses perkembangan dalam pembentukan identitas spiritual. Sejalan dengan itu, tujuan dari penelitian ini adalah untuk mendeskripsikan proses pembentukan identitas spiritual Paulo. Penelitian ini menggunakan pendekatan psikososial oleh Erik H. Erikson untuk menganalisis masalah. Berdasarkan hasil analisis, studi ini menunjukkan bahwa ada beberapa langkah dalam proses perkembangan pembentukan identitas spiritual. Kata Kunci: spiritualitas, agama, identitas spiritual Abstract The identity formation concerns develop during the adulthood stage. The concerns include vocational, political, religious/spiritual, and sexual issues. As one of the concerns of identity formation, spirituality covers the major issues in identity formation of adulthood. Spirituality contributes an important role in identity formation. Spirituality brings an awareness of self in relationship to others. Engaging in the spiritual provides connectedness with divine, human, or natural other, giving individuals an opportunity to experience himself or herself in relationship to God, a community of believers, or nature. Paulo’s search of his spiritual identity has led him to fulfill the developmental tasks of spiritual identity formation. In line with that, the purpose of this study is to describe the process of Paulo’s spiritual identity formation. This study uses psychosocial approach by Erik H. Erikson to analyze the problem. Based on the analysis, this study shows that there several steps in the developmental tasks of spiritual identity formation. Keywords: spirituality, religion, spiritual identity. INTRODUCTION One of the most successful and popular writers in the recent years is Paulo Coelho. Paulo Coelho was born in Rio de Janeiro, Brazil on August 24, 1947. He was a journalist, an actor and a theatre director before becoming an author. His personal and spiritual lives give a big influence to most of his works. For instance, The Pilgrimage (1988), The Alchemist (1988), and Aleph (2011) seem to be his biographical novels. These novels were written based on his personal and spiritual life. As for Aleph it looks like a documentation of his personal and spiritual journey after making a catholic pilgrimage to Spain. Coelho also claimed that these novels are the adaptation of his own spiritual journey. In the novel Aleph, Paulo is pictured as a fifty-nine years old man and also a successful writer who has achieved everything in his life except one thing, he feels something wrong about himself. He thinks that he is not what he wants to be and considers himself to be in the wrong path. Generally known, people of his age should have a fixed identity since the identity forming happens in adolescence. Yet in this case, adulthood people perhaps have different opinion about identity. In adolescence, identity is defined as who one is and where his place in this world. As time passes by, adolescents will grow old and may change their perception about their identity. Identity is no longer a mere question about “Who am I?”, rather it concerns with religious and spiritual matters. As Erikson (in Hoare, 2002), identity does not end in adolescence. He says that identity is a progressing process that happens throughout the stages of adulthood. In other words, identity is not really fixed in adolescence and it is an evolving aspect of adulthood life which continues to renew as time goes by. As Erikson (in Hoare,2002) suggests that identity could change during the adulthood stage due to life experiences that one encounters, the identity formation in adulthood is flexible to modify and evolve due to individuals’ experiences. It tends to be a development of the previous stage in which identity has been formed in the adolescence. One of identity issues of adulthood is spiritual/religious identity. Generally, there is an unclear distinction between spirituality and religion, but there is a different point between the two domains. Contemporary research often attempts to differentiate religion from spirituality. In this case, religion generally becomes associated with the institutional and the sociological (prescribed systems, rituals, and traditions or beliefs), and spirituality becomes associated more with personal, psychological, and individual phenomena (Hood, Spilka, Hunsberger, & Gorsuch, 1993). In the spiritual identity formation, the two domains, spirituality and religion contribute an importing as wholeness. Indeed, all dimensions of spirituality can be addressed by religion as well as by other ideologies and practices (Roehlkepartain et al., 2006). Identity formation in adulthood, as Erikson (1968) notes it, has the same methodology as the other stages do. It begins with identification /exploration of individuals about the outer world (society) to coin a sense of identity. Then it is followed by conflicts and crises as Erikson (1968) has stated that conflicts and crises are psychosocial needs in nature. Given the right condition and enough time and space, individuals may achieve a balanced perspective of identity of what they need to be and what the society expects them to be, therefore identity has been formed. Nonetheless, based on facts laying on the background of the study above, then the problem is stated in: (1) how is Paulo’s spiritual identity in Paulo Coelho’s Aleph viewed by Erikson’s concepts of spirituality? As referred to the background and statement of the problem above, the objective of the study is devoted to know a purpose as results of analyzing the problem: (1) to describe the process of spiritual identity formation of Paulo in Paulo Coelho’s Aleph viewed by Erikson’s concepts of spirituality. In accordance, it is expected that this study can give both theoretical and practical significance. In theoretical significance, Paulo Coelho’s Aleph contains issues regarding spiritual identity formation. Therefore, this study is expected to give positive contribution towards the development of literary theory, which studies literature and society under the concepts of spirituality and personality development. Additionally, in practical significance, this study is expected to contribute to the practice of analyzing literary works by applying proper literary concept and theory. Hopefully, to whom this study may concern, it can be used as reference. Furthermore, this study expectantly can assist the institution to provide rich collection of research references. RESEARCH METHOD To collect the data, the first step is doing close reading the novel entirely. It is done over and over in order to be able to catch and understand the core story—intrinsically and extrinsically—of the novel. Besides, it also aims to support in collecting and analyzing the statement of the problems later on. Secondly, it comes to the step of collecting data. At this point, the data is collected through noting the narration and characters’ dialogue and action in the novel, which reflects the idea of the process of spiritual identity formation in the form of quotation. To simplify the analysis of this study, there are two important steps needed to be done. The first is describing the facts. At this point, the facts are the data in the novel which supports the study or the statement of the problem. It is done by describing the collected data based on the subject of this study—spiritual identity formation of Paulo. Last but not least, the second is doing analysis towards the described data. It will dig the information beyond the data deeper by explaining it thoroughly. It is taken from the data in the novel first and, then, it will be analyzed by based on the thought of the researcher. At this point, to make best explanation and understanding of the study, Erikson’s concepts of spirituality are included. ERIKSON’S CONCEPTS OF SPIRITUALITY Erikson (in Hoare, 2002) states that identity development does not end in the adolescence stage. He views identity as a progressing process that evolves throughout the stages of adulthood. Therefore, identity development is considered as a normative period of adolescence and evolving aspects of adulthood. Many experts disagree with his statement. They claim that identity is fixed at the end of adolescence stage. However, Erikson proposes that identity formation of adolescence does not remain fixed. He adds that identity formation holds a flexibility to modify throughout the adulthood stage. That is why he states that identity development does not end at the end of adolescence stage. Erikson suggests that identity could change during the adulthood stage due to life experiences that one encounters. Identity formation in adulthood, as Erikson (1968) notes it, has the same methodology as the other stages do. It begins with identification /exploration of individuals about the outer world (society) to coin a sense of identity. Then it is followed by conflicts and crises as Erikson (1968) has stated that conflicts and crises are psychosocial needs in nature. Given the right condition and enough time and space, individuals may achieve a balanced perspective of identity of what they need to be and what the society expects them to be, therefore identity has been formed. The identity formation concerns develop during the adulthood stage. The concerns include vocational, political, religious/spiritual, and sexual issues. As one of the concerns of identity formation, spirituality covers the major issues in identity formation of adulthood. As Erikson (1968) and Loder (1998) suggest, the beliefs, worldview, and values of religious traditions provide an ideological context in which individuals can generate a sense of meaning, order, and place in the world that is crucial to identity formation. Moreover, spirituality contributes an important role in identity formation. Spirituality brings an awareness of self in relationship to others (Benson, 1997). Engaging in the spiritual provides connectedness with divine, human, or natural other, giving a young person an opportunity to experience himself or herself in relationship to God, a community of believers, or nature for example. This moving beyond the self provides the opportunity for the search for meaning and belonging that is central to the task of identity exploration (Benson, 1997; Hill et al., 2000). Erikson (1965) adds that awareness that stems from this search provides the ultimate answers and perspective in the larger issues of life that are crucial to the resolution of identity crisis. In this sense, spiritual identity can refer to a connectedness to both divine and human. In achieving the spiritual balance, Erikson (in Hoare, 2002) introduces the images of the spiritual adult involved holistic concepts such as (1) actuality and mutuality: the release of defensiveness naturally acquired in attaining autonomy that frees one to participate and share effectively; (2) leeway: the freedom to be oneself and to grant such freedom to others; (3) adaptation: the move from passive acceptance of unacceptable life conditions to ego strength whereby one gains the power to fit the environment to one’s needs and the needs of others; (4) insight: truth gained via contemplation of seeing into oneself and into a situation that it obliges toward ethical action; and (5) virtue and centrality: the spiritual and ethical center that with optimum resolution of life stages allows the self to be bound together around transcendent values of hope, purpose, fidelity, love, wisdom, and so on. PAULO’S SPIRITUAL IDENTITY FORMATION One of this study concerns is to describe how identity is defined in Paulo Coelho’s Aleph by analyzing the character of Paulo. In the novel, Paulo is pictured as a fifty-nine years old man and also a successful writer who has achieved everything in his life except one thing, he feels something wrong about himself. He thinks that he is not what he wants to be and considers himself to be in the wrong path. Generally known, people of his age should have a fixed identity since the identity forming happens in adolescence. Yet in this case, adulthood people perhaps have different opinion about identity. In adolescence, identity is defined as who one is and where his place in this world. As time passes by, adolescents will grow old and may change their perception about their identity. Identity is no longer a mere question about “Who am I?”, rather it concerns with religious and spiritual matters. As Erikson (in Hoare, 2002) earlier suggests, identity does not end in adolescence. He says that identity is a progessing process that happens throughout the stages of adulthood. In other words, identity is not really fixed in adolescence and it is an evolving aspect of adulthood life which continues to renew as time goes by. As Erikson (in Hoare,2002) suggests that identity could change during the adulthood stage due to life experiences that one encounters, the identity formation in adulthood is flexible to modify and evolve due to individuals’ experiences. It tends to be a development of the previous stage in which identity has been formed in the adolescence. One of identity issues of adulthood is spiritual/religious identity. Generally, there is an unclear distinction between spirituality and religion, but there is a different point between the two domains. Contemporary research often attempts to differentiate religion from spirituality. In this case, religion generally becomes associated with the institutional and the sociological (prescribed systems, rituals, and traditions or beliefs), and spirituality becomes associated more with personal, psychological, and individual phenomena (Hood, Spilka, Hunsberger, & Gorsuch, 1993). In the spiritual identity formation, the two domains, spirituality and religion contribute an importing as wholeness. Indeed, all dimensions of spirituality can be addressed by religion as well as by other ideologies and practices (Roehlkepartain et al., 2006). Identity formation in adulthood, as Erikson (1968) notes it, has the same methodology as the other stages do. It begins with identification /exploration of individuals about the outer world (society) to coin a sense of identity. Then it is followed by conflicts and crises as Erikson (1968) has stated that conflicts and crises are psychosocial needs in nature. Given the right condition and enough time and space, individuals may achieve a balanced perspective of identity of what they need to be and what the society expects them to be, therefore identity has been formed. In the novel Aleph, Paulo is beginning to search the meaning of his spirituality by conducting identifications, exploration and experiments through magical and religious traditions to discover his spiritual identity. Erikson (1965) states that ne way religion promotes a sense of belongingness is through religious rituals. In this case, Paulo conducts magical and religious traditions in order to search the meaning of his spiritual being. It has made Paulo engage into a man named J. who serves as his master. The purpose of these rituals/traditions, as Erikson states it, is to promote a sense of belongingness of Paulo. In the other words, it leads Paulo to where his spirituality belongs to. Still in the same subject, what individuals need are exploring and experiment that provide them the opportunity to search the meaning of their belongingness in spiritual context. In order to explore and experiment his spiritual life, Paulo has taken the road of a pilgrim since he was a teenager. He traveled continents to search the meaning of his spiritual being and now he comes to a point where he finally understands that in order to search his spiritual being, he has to explore and experiment with his spirituality by following religious paths. As Erikson (1968) and Loder (1998) suggest, the beliefs, worldview, and values of religious traditions provide an ideological context in which individuals can generate a sense of meaning, order, and place in the world that is crucial to identity formation. Religion in Paulo’s life has been becoming meaningful since he took the paths of Pilgrim since he was young. As what Erikson and Loder have stated, one way individuals can generate a sense of meaning of self is by exploring and experimenting the values of religious traditions in which Paulo has followed for years. Guided by J, Paulo has followed the religious traditions to regain the touch of his inner being/spirituality. Besides performing that religious tradition as mentioned above, spirituality can also be achieved by doing the other religious traditions such as performing confessional prayers, going to church, mosque and temple, or following the path of Pilgrimage. Since Paulo believes in Christianity, he follows the Pilgrimage Path to search his spiritual identity. This, as Erikson calls it “developmental task”, is the process of exploring and experimenting to re-establish identity. The developmental tasks of finding spiritual identity are determined by the gradual process of the individuals’ spiritual or religious experiences. Thus, Paulo’s effort by following the religious traditions has put him in the correct order to attain his spiritual identity. Referring to the meaning of religion as mentioned above, a person may experience and generate a sense of belonging to God or a community of believers. This moving beyond the self provides the opportunity for the search for meaning and belonging that is central to the task of identity exploration (Benson, 1997; Hill et al., 2000). Thus, it proves that religion promotes a central role to spiritual identity formation. Religion helps the individual to achieve the connectedness to the Divine. In this case, Paulo has achieved the connectedness to the Divine by performing religious traditions. The developmental tasks of identity formation in spiritual context do not end by only achieving the connectedness to the Divine. There is more to do before achieving the spiritual identity. The next developmental tasks are to build the connectedness to the other human being. This kind of connectedness is personal and psychological in nature. According to Benson (1997), spirituality contributes an important role in identity formation. Spirituality brings an awareness of self in relationship to others. Therefore, spirituality helps the individuals to fulfill the developmental tasks and achieving the connectedness to the others. In achieving the spiritual balance, Erikson (in Hoare, 2002) introduces the images of the spiritual adult involved holistic concepts such as (1) actuality and mutuality: the release of defensiveness naturally acquired in attaining autonomy that frees one to participate and share effectively; (2) leeway: the freedom to be oneself and to grant such freedom to others; (3) adaptation: the move from passive acceptance of unacceptable life conditions to ego strength whereby one gains the power to fit the environment to one’s needs and the needs of others; (4) insight: truth gained via contemplation of seeing into oneself and into a situation that it obliges toward ethical action; and (5) virtue and centrality: the spiritual and ethical center that with optimum resolution of life stages allows the self to be bound together around transcendent values of hope, purpose, fidelity, love, wisdom, and so on. Related to the five images of Erikson’s adult spiritual, there seems to be compatibility between those characteristics and Paulo’s spirituality regarding to build connectedness or harmony to the others. In Paulo’s case, he builds relationships with the others to keep in touch with his inner self and his surroundings (people and environments). Having followed the path of religion, he chooses the method of his beliefs to gain his spirituality in the matter of connecting with the others by making relationships with people and his surroundings. Therefore, in order to make relationships with the others, Paulo decides to have a meeting with people he has never met before after book signing session. Relating those efforts from Paulo to the images of spiritual adult introduced by Erikson, Paulo has attained the first image as a spiritual adult, which is actuality and mutuality. Paulo releases his defensive nature to gain the autonomy as an independent person that frees him to share and participate in the party. His efforts have put him to the foundation of spiritual being of his self in relation with the others. Thus, after achieving the stage of actuality and mutuality, adults have to pass the other gradual processes in forming the spiritual identity. As Erikson (in Hoare, 2002), there are five images of spiritual adults in the adulthood stages. Those images can only be achieved by experiencing gradual processes. As Paulo moves forward in the developmental tasks, he finds that actuality and mutuality do not meet his spiritual needs. He needs to experience more spiritual processes to attain the awareness of self in spirituality. He goes forward and experiments his spiritual side by conducting more chances to meet people. Yet it seems to him, there is a woman that could be the key to explore deeper his spiritual life and the woman is Hilal. Through Hilal point of view, Paulo has already met her in past lives. Yet Paulo rejects Hilal’s existence and the fact that they are bound together in this life. This leads Paulo to a state of desperation. Erikson (1968) refers to the developmental tasks of this condition as ego integrity versus despair. In this case, despair is the crisis in the developmental tasks of adulthood. These tasks involve the integration of all elements of the past and the acceptance that this is the only life to be lived. In Paulo’s case, he denies the fact that he was bound to Hilal in the past times and neglecting Hilal’s presence in the present time. Being in the state of desperation, Paulo is haunted by the past lives and tries to recollect solve the maze of his past lives. According to Erikson (1968), the goal of this time in life is to be able to look back on life as meaningful and fulfilling. Yet, Paulo is striving to complete these developmental tasks. In these circumstances, as what Erikson suggests, Paulo has to be able to integrate all elements of his past. In this case, Paulo seems to have contradiction towards Hilal about their past lives. In Paulo’s point of view, he was priest who had made several women sentenced to death because he did not testify that the women were innocent. In the other hand, according to Hilal, Paulo was the priest and the man she loved that made him burned to death and he was responsible for doing that. As Erikson (1968) has already assumed, conflicts or crises are in nature in psychosocial. The conflicts between the two in contradicting their past lives promotes to them to a deeper spiritual side of them. Through The Aleph, they are reliving their past in a fraction of seconds. The goal of this effort, as what Erikson suggests, is to look back on life as meaningful and fulfilling. After several time revisiting the past lives, Paulo come into a realization that the goal and the meaning of this life was to fulfill the unfinished tasks from his past. He realizes that the pilgrimage leads him to fulfill his redemption for making those women in past suffer. Thus, Paulo has managed this Ego integrity versus despair. Succeeding in his developmental tasks so far, Paulo has reviewed his contributions he made to the others. Besides having form the integration of his past live, Paulo is really fulfilling Erikson’s third image of spiritual adult, which is adaptations. Erikson (in Hoare, 2002) refers adaptations to the move from passive acceptance of unacceptable life conditions to ego strength whereby one gains the power to fit the environment to one needs and the needs of others. By receiving Hilal, forgiveness, Paulo has attained Erikson’s image of adaptations because he has finally accepted his life conditions where he has to fulfill his redemption in this time of life. Thus, he gains the power to fit environment to his needs as an independence being and the need of other (Hilal). Those descriptions of Paulo’s efforts in search of his spirituality have put him to the connectedness to the Divine and the human. Yet, Paulo has not gained the spiritual identity though he has gone through gradual processes of spirituality and religion. The final task of the developmental tasks is to integrate the concept of spirituality (connectedness to others) and religion (connectedness to the Divine) wholeness or unity. Religion and spirituality seeks to integrate rather than polarize. Therefore, spiritual identity is not only inclusive religious beliefs and practice but may also involve pathways and sacred not found in religion (Zinnbauer, Pargament, & Scott, 1999). To discover the ultimate answer of the developmental tasks, Paulo is brought to an island in the middle of Lake Baikal. The ultimate answer is similar to that Erikson’s fifth image of spiritual adult, which is virtue and centrality. This image refers to the integration of spiritual ethical center that allows the self to be bound together around transcendent values hope, purpose, fidelity, love and wisdom. In the other words, if one has achieved this image of spiritual adult, therefore spiritual identity is formed. In the island, Paulo meets a shaman that guides him to engage in a traditional spirituality tradition that allows him to integrate the religious side and spiritual side of his self to achieve the ultimate answer of his search. Engaging in such spiritual tradition, Paulo has been aware of what he is and where his spiritual side leads him to. As what Erikson (1968) assumes, engaging in the spiritual provides connectedness with divine, human, or natural other, giving a young person an opportunity to experience himself or herself in relationship to God, a community of believers, or nature. Thus, Paulo’s engagement to the shaman in the spiritual tradition has brought him awareness of his spiritual and religious being. Awareness that stems from this search provides the ultimate answers and perspective in the larger issues of life that are crucial to the resolution of identity crisis. Therefore, Paulo’s spiritual identity has been formed after going through gradual processes of spirituality and religion. It concludes that the identity formation of Paulo is completed. CONCLUSION Based on the recent analysis of the data, the result can be concluded that Paulo has to encounter gradual process before achieving the spiritual identity. The gradual process is simplified into several steps. The first step is doing exploration and experiment. In this case, Paulo is engaging in religious tradition to explore and experiment his spiritual side. Secondly, the step is achieving Erikson’s images of spiritual adult. From the analysis, Paulo has achieved three of five images of spiritual adult. The images are (1) actuality and mutuality, (2) adaptation, and (3) virtue and centrality. Thirdly, the step is facing crisis (despair). Paulo turns to despair when he cannot find the harmony between his religious and spiritual values. Besides, he is also conflicting with Hilal. The Last step is integrating religious and spiritual values (ego integrity) and discovering spiritual identity. Paulo has managed to integrate the religious and spiritual values. Therefore, Paulo is completing the spiritual identity formation. REFERENCES Benson, P. L. 1997. Spirituality and the adolescent journey. Reclaiming Children and Youth, 5, 206–209. Erikson, E. H. 1965. Youth: Fidelity and diversity. In E. H. Erikson(Ed.), The challenges of youth (pp. 1–28). Garden City,NY: Anchor. Erikson, Erik H. 1968. Identity, youth, and crisis. New York: Norton. Hill, P. C., Pargament, K. I., Hood, R. W., McCullough, M. E., Swyers, J. P., Larson, D. B., et al. 2000. Conceptualizing religion and spirituality: Points of commonality, points of departure. Journal for the Theory of Social Behavior, 30, 51–77. Hoare, C. H. 2002. Erikson on development in adulthood: New insights from the unpublished papers. New York: Oxford University Press. Hood, R.W., Spilka, B., Hunsberger, B., & Gorsuch, R. 1996. The psychology of religion: An empiricalapproach (2nd ed.). New York: Guilford. Loder, J. E. 1998. The logic of the spirit: Human development in a theological perspective. San Francisco: Jossey-Bass. Roehlkepartain, E. C., King, P. E.,Wagener, L., & Benson, P. L. (Eds.). 2006. The handbook of spiritual development in childhood and adolescence. Thousand Oaks, CA: Sage. Zinnbauer, B. J., Pargament, K. I., & Scott, A. B. 1999. The emerging meanings of religiousness and spirituality: problems and prospects. Journal of Personality, 67, 889–916.